Chapter Antagonism and Coexistence. Local Population and Western Merchants On Venetian Azov Sea in the 14th century - Pubblici, Lorenzo (Biblioteca di Studi Slavistici, 2017)
The commercial expansion of Venice intersected with the rapid formation of the Mongol Empire, which, starting from the 1240s, extended from China to the gates of Europe. The constitution of a homogeneous and vast political entity integrated regional economies and facilitated communications. In Tana, the easternmost Venetian settlement at the mouth of the Don River, the Western urban mercantile class met the locals in a remote geographical area. This paper analyzes the relationships between Venetians and Westerners in general on the one side, and the local population on the other in the 14th century.